Morphological evolution driven semiconducting nanostructures for emerging solar, biological and nanogenerator applications. Issue 22 (19th October 2022) - Srivastava, Avanish Kumar; Tawale, Jai Shankar; Verma, Rajni; Agarwal, Daksh; Sharma, Charu; Kumar, Ashavani; Gupta, Manoj Kumar
Abstract : Metal oxide nanostructures are extremely fascinating smart and functional materials owing to their outstanding wide and tunable band gap, biocompatibility, high electrochemical coupling coefficient, photostability and excellent piezoelectric properties. Abstract : Metal oxide nanostructures are extremely fascinating smart and functional materials owing to their outstanding wide and tunable band gap, biocompatibility, high electrochemical coupling coefficient, high photostability, high sensitivity, non-toxicity, high electron mobility and high thermal/chemical stability properties. The morphologies of the metal oxide nanostructures are highly influenced by growth parameters and methods. The performance of solar cell/sensors, biological, electronic and energy harvesting properties are highly varied with the morphological changes in the nanostructures. The progress of the metal oxide nanostructures for particular applications has been discussed in many earlier review articles; however, a comprehensive review article based on the various morphologies of metal oxide nanostructures (especially, together with ZnO and SnO2 ) for their numerous and next-generation applications has not been reported yet. The present review article summarizes the recent progresses and applications of ZnO and SnO2 nanostructures to provide a comprehensive understanding of the effect of morphologies on the performance of the technological devices and biosensors. The growth of various nanostructures (such as tetrapods, nanorods and nanowires) and their wide applications in solar cells, biological field, sensors and piezoelectric nanogenerators/piezotronics are covered in the present review. This review also provides a detailed comparison of the performances of ZnO nanostructure-based solar cells with SnO2 -based solar cells and flexible devices. The performance of the solar cell in terms of morphology, electron mobility, band gap and piezoelectric properties are also discussed. This paper also gives insights into the antimicrobial, antilarvicidal and anticancer activities of various ZnO and SnO2 nanostructures. In addition, special deliberation has been made on the fabrication of novel piezoelectric nanogenerators based on the various morphologies of ZnO (such as nanowires, nanosheets and nanorods) for scavenging mechanical energy from the living environment. Finally, the benefits, challenges and future outlook of metal oxide nanostructures for their potential application in opto-electronic, sensors, biomedical energy harvesting and next-generation flexible self-powered nanosystems are highlighted.